ANALISIS RANTAI PASOKAN MENTIMUN DI PASAR INDUK KOTA SURAKARTA - Muslim, Aditya Fadilla; Widadie, Fanny; Sutrisno, Joko (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2024)
Agricultural commodities have supply chain flows from upstream to downstream, namely from producers to consumers. The need for vegetables in the city of Surakarta must be met by the surrounding area because of the limited agricultural land in the city of Surakarta itself. One of the vegetable commodities supplied is cucumber. Therefore, it is important to know the flow of the cucumber supply chain in the Central Market of Surakarta City. The research method used is descriptive quantitative. The research location was chosen purposively, namely the Central Market of Surakarta City (Pasar Gede and Pasar Legi). The sampling technique used snowball sampling to collect informants consisting of farmers, collectors, wholesalers and retailers and incidental sampling with the Slovin formula so that the number of respondents was 77 traders. Data collection techniques using interviews, questionnaires, and documentation. Data analysis used descriptive analysis and multiple linear regression test. The results of this study are 1) there are 6 flows of goods in the supply chain with farmers, collectors, wholesalers, retail traders andconsumers, the financial flow is divided into 2, namely early and late repayment and the flow of information occurs in 2 directions, namely information from farmers to traders. (cucumber availability and transaction mechanisms) and from traders to farmers (price developments). 2) the majority of traders supply cucumbers of 350 - 586 kg. 3) thefactors that have a significant effect on the supply volume of cucumbers in the Central Market of Surakarta City areprice, profit, transportation, supplier area and quality.